The impact of Epstein‐Barr virus latent membrane protein 2A on the production of B cell activating factor of the tumor necrosis factor family (BAFF), APRIL and their receptors. Issue 11 (26th October 2022) - Madayag, Kevin; Incrocci, Ryan; Swanson‐Mungerson, Michelle
Abstract: Introduction: Epstein‐Barr virus (EBV) establishes a lifelong infection in human B cells where the virus consistently expresses Latent Membrane Protein 2A (LMP2A) to promote B cell survival. A prior study indicates that LMP2A may increase the production of the pro‐survival factor, B cell Activating Factor of the tumor necrosis factor family (BAFF), which could also indirectly increase B cell survival. The current study sought to extend these findings and determine if LMP2A increased BAFF production and/or the responsiveness of LMP2A‐expressing cells to this cytokine. Methods: Four independently derived LMP2A‐negative and ‐positive B cell lymphoma cell lines were analyzed for BAFF and APRIL levels by both ELISA and Western Blot analysis. Additionally, flow cytometric analysis measured any LMP2A‐dependent changes in the receptors for BAFF and APRIL (BAFF‐R, transmembrane activator and calcium‐modulator and cyclophilin ligand interactor [TACI], B cell maturation antigen [BCMA]) in both LMP2A‐negative and ‐positive B cell lymphoma cell lines. Results: In contrast to previous reports, our data indicate that LMP2A does not increase the expression of BAFF or APRIL by Western blot analysis or ELISA. Additionally, flow cytometric analysis indicates that LMP2A does not influence the expression of the receptors for BAFF and APRIL: TACI, BAFF‐R, and BCMA. Conclusion: Therefore, these data suggest that while EBV utilizes other latency proteins to regulate BAFF production, EBV does not appear to use LMP2A to enhance BAFF‐or APRIL‐dependent survival to promote EBV latency. Abstract : In contrast to previous reports, Latent Membrane Protein 2A (LMP2A) does not increase B cell Activating Factor of the tumor necrosis factor family (BAFF) or APRIL production and/or its receptors. Since LMP2A is expressed in Epstein‐Barr virus‐associated autoimmune diseases, this suggests that the BAFF/APRIL axis is not influenced by LMP2A to promote autoimmune disease.